2019
DOI: 10.3390/molecules24224190
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Molecular Imaging of Opioid Receptors

Abstract: The discovery of endogenous peptide ligands for morphine binding sites occurred in parallel with the identification of three subclasses of opioid receptor (OR), traditionally designated as μ, δ, and κ, along with the more recently defined opioid-receptor-like (ORL1) receptor. Early efforts in opioid receptor radiochemistry focused on the structure of the prototype agonist ligand, morphine, although N-[methyl-11C]morphine, -codeine and -heroin did not show significant binding in vivo. [11C]Diprenorphine ([11C]D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 217 publications
(233 reference statements)
0
35
0
Order By: Relevance
“…We observed significant increases in plasma cortisol and in pituitary R1 (see the “Methods” section) that were consistent with HPA hyperactivity during NPW [ 78 ]. Opioid and DA receptors modulate HPA function [ 79 ], for example, MOR is highly expressed in the pituitary [ 40 ]. The positive association between increases in pituitary R1 and striatal DA release could reflect concomitant effects of NAL on the pituitary and DA systems [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed significant increases in plasma cortisol and in pituitary R1 (see the “Methods” section) that were consistent with HPA hyperactivity during NPW [ 78 ]. Opioid and DA receptors modulate HPA function [ 79 ], for example, MOR is highly expressed in the pituitary [ 40 ]. The positive association between increases in pituitary R1 and striatal DA release could reflect concomitant effects of NAL on the pituitary and DA systems [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also performed exploratory analyses to assess the effect of NPW on R1 in the pituitary and habenula ROIs. The pituitary has high MOR levels [ 39 , 40 ], is a major source of endorphins (endogenous MOR agonist), and modulates the HPA response during NPW. Increases in pituitary R1 (measured with PET) have been observed in conditions that trigger the release of pituitary hormones [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Technically, while [ 11 C]carfentanil BP ND in baseline condition is proportional to MOR density, the exact contributions of MOR density, receptor affinity, and baseline occupancy by endogenous opioids cannot be assessed in a single measurement ( Mintun et al, 1984 ; Henriksen and Willoch, 2008 ), and these components cannot be differentiated in a single scan. [ 11 C]carfentanil is an agonist tracer preferably binding MORs in the high-affinity state ( Henriksen and Willoch, 2008 ; Cumming et al, 2019 ) and has low test–retest variability in PET imaging ( Hirvonen et al, 2009 ). Although endogenous opioids compete for binding sites with [ 11 C]carfentanil ( Quelch et al, 2014 ; Saanijoki et al, 2018 ), the basal opioid concentrations are often very low, at least in rats ( Maidment et al, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…[8] Recently, Lever et al reported the synthesis and opioid receptor binding properties of 111 In-labelled diprenorphine DOTA conjugates for imaging by means of single photon emission computer tomography (SPECT). [9] In the last two decades, comprehensive reviews [8,[10][11][12] have summarized the diversity of radiotracers available in the field of opioid receptor imaging.…”
Section: Introductionmentioning
confidence: 99%